Criminal Act of Severe Assault by PS Towards M Reviewed Under Law Number 13 of 2006 jo Law Number 31 of 2014 Concerning the Protection of Witnesses and Victims - Blaviando, Edo; Christianto, Hwian; Siwu, Sonya Claudia (LPPM Universitas Ekasakti Padang, 2024)
This research aims to analyze the Criminal Act of Severe Assault by PS towards M based on Law Number 13 of 2006 jo Law Number 31 of 2014 concerning the Protection of Witnesses and Victims. The research method used is a juridical normative legal research type with a statute and conceptual approach. The primary data source is primary legal materials such as the Criminal Code and the Law on the Protection of Witnesses and Victims. The results of the research indicate the urgency of protecting witnesses and victims of criminal acts in criminal law as an effort to uphold human rights. Protection for victims of severe assault crimes needs to be strengthened through clear and effective regulations to provide a sense of security and justice for the victims. In conclusion, the protection of witnesses and victims of criminal acts is an integral part of the criminal justice system aimed at providing justice, preventing threats, and ensuring the fulfillment of victims' rights. Further efforts are needed to strengthen the protection of victims of criminal acts, including severe assault crimes, in accordance with legal principles and human rights.